2021
DOI: 10.18632/aging.202761
|View full text |Cite
|
Sign up to set email alerts
|

A five-m6A regulatory gene signature is a prognostic biomarker in lung adenocarcinoma patients

Abstract: We analyzed the prognostic value of N6-methyladenosine (m6A) regulatory genes in lung adenocarcinoma (LADC) and their association with tumor immunity and immunotherapy response. Seventeen of 20 m6A regulatory genes were differentially expressed in LDAC tissue samples from the TCGA and GEO databases. We developed a five-m6A regulatory gene prognostic signature based on univariate and Lasso Cox regression analysis. Western blot analysis confirmed that the five prognostic m6A regulatory proteins were highly expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Moreover, low m 6 A score, characterized by increased mutation burden and activation of immunity, indicates an inflamed TME phenotype and enhanced response to anti-PD-1/L1 immunotherapy in gastric cancer (GC) (65). In addition, m 6 A-related signature has been identified as biomarker for tumor immune phenotypes and anti-PD-1 immunotherapy treatment response in lung adenocarcinoma (LADC) (72,73), stomach adenocarcinomas (STADs) (74), Esophageal squamous cell carcinoma (ESCC) (75,76), Renal Papillary Cell Carcinoma (RPCC), Hepatocellular Carcinoma (HCC) (77,78). These statistic results together indicate that m 6 A modification may reflect TME status and predict immunotherapy efficacy in pan-cancers instead of limited to specific cancer types.…”
Section: Role Of M 6 a In Tme Immune Responsementioning
confidence: 99%
“…Moreover, low m 6 A score, characterized by increased mutation burden and activation of immunity, indicates an inflamed TME phenotype and enhanced response to anti-PD-1/L1 immunotherapy in gastric cancer (GC) (65). In addition, m 6 A-related signature has been identified as biomarker for tumor immune phenotypes and anti-PD-1 immunotherapy treatment response in lung adenocarcinoma (LADC) (72,73), stomach adenocarcinomas (STADs) (74), Esophageal squamous cell carcinoma (ESCC) (75,76), Renal Papillary Cell Carcinoma (RPCC), Hepatocellular Carcinoma (HCC) (77,78). These statistic results together indicate that m 6 A modification may reflect TME status and predict immunotherapy efficacy in pan-cancers instead of limited to specific cancer types.…”
Section: Role Of M 6 a In Tme Immune Responsementioning
confidence: 99%
“…Multiple studies have performed exhaustive analyses of the relationship between m6A regulator expression and epidemiological data of cancer patients from TCGA. Among the cancer types examined were colorectal cancer (35), hepatocellular carcinoma (36), and lung adenocarcinoma (37). At present, there are no studies on the correlation between m6A regulator expression and ESCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [ 17 ] used univariate and LASSO Cox regression analysis to develop a m6A regulator prognostic signature composed of HNRNPC, METTL3, HNRNA2B1, IGF2BP1, and IGF2BP2 for lung adenocarcinoma based on RNA-seq, clinicopathological, and single nucleotide variation data retrieved from the TCGA database. [ 17 ] Also, Yang et al [ 18 ] found that HNRNPC and KIAA1429 can be regarded as potential prognostic markers in papillary renal cell carcinoma by using the similar method. However, only few studies have investigated the prognostic value of m6A regulators in UCEC.…”
Section: Discussionmentioning
confidence: 99%